Solving the ally-versus-acquire dilemma through the dual lenses of subjective and objective views - Tseng, Chiung-Hui (Journal of Business Economics and Management, 2017)
Nowadays many firms seek hard-to-imitate assets via allying with or acquiring other firms that own desired resources. As such, how to choose between alliances and acquisitions becomes a critical decision, and one important determinant is interfirm factors. This study probes three crucial yet underexplored interfirm differences, and develops scales to capture managers’ perceptions of the differences that, based on managerial cognition literature, dictate the ally-versus-acquire choice. Further, we argue that managers adjust their judgement across varying objective conditions. Each perceived difference is thus paired with a moderator identified respectively from the resource-based view, competitive dynamics, and collaborative capability literature. Evidences on Taiwanese firms show that a larger resource-deployment difference enhances acquisition likelihood, while greater differences in marketing praxis and human resource management increase alliance formation. Moreover, the resource-deployment difference leads to alliances for relatively younger partners, and the difference in human resource management favors acquisitions when focal firms have more interfirm governance experience.